(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the concept of sentence typology and clause structure within the framework of Cognitive Grammar, a theory developed by Ronald Langacker. The focus is on how different clause types—declarative, interrogative, imperative, and exclamative—serve distinct communicative functions and reflect human cognitive processes. Cognitive Grammar posits that grammar is not a set of abstract syntactic rules but is closely tied to the ways in which speakers mentally conceptualize and organize their experiences. The article discusses how the structure of a clause in Cognitive Grammar is organized around profiles (the central conceptual focus) and base domains (the broader contextual information), highlighting how different clause types influence cognitive focus and interaction. It also examines the fundamental structures like Subject-Verb-Object (SVO) and Subject-Verb-Complement (SVC), exploring how these syntactic patterns mirror cognitive processes such as event categorization and role assignment. Additionally, the article emphasizes the dynamic nature of clause structure, showing how the organization of a sentence is not fixed but adaptable to the speaker’s communicative needs. By analyzing how language is structured around conceptualization, the article argues that Cognitive Grammar provides a holistic view of how sentence structures function not just as formal systems but as tools for representing and sharing knowledge. This work contributes to a deeper understanding of the intersection between language and cognition, revealing how grammatical structures reflect our mental models of the world and facilitate effective communication.